HUBUNGAN STRES DENGAN KEJADIAN STOMATITIS AFTOSA REKUREN PADA MAHASISWA AKTIVIS POLTEKKES KEMENKES BANDUNG - Sya'diyah, Rainanda Nabilatu; Widyastuti, Tri; Restuning, Sekar (Poltekkes Kemenkes Bandung, 2024)
Background: Recurrent Aphthous Stomatitis (SAR) is an inflammatory condition that occurs in the oral mucosa, in the form of yellow-white ulcers, one of the causes of which is stress. Stress is a state of mental and emotional disturbance or chaos that is usually often experienced by student activists due to pressure in both the academic and non-academic fields. Methods: The type of research used is observational analytic with a cross-sectional approach. The research was conducted at the Poltekkes Kemenkes Bandung with a sample of 94 student activists who were taken using purposive sampling with simple random sampling technique. This study aims to determine the relationship between stress and the incidence of recurrent aphthous stomatitis in student activists. Results: Univariate data analysis is presented in the form of frequency distribution and bivariate analysis using chi-square. The level of stress in the moderate category was experienced by 59 people (62%) who were dominated by women (50%). Respondents who did not experience SAR were 50 people (53.6%). The results of the chi-square test analysis showed a p-value = 0.000 Conclusion: There is a relationship between stress and the incidence of recurrent aphthous stomatitis in activist students of the Poltekkes Kemenkes Bandung. This can occur because stress can affect the immune system and increase the risk of inflammation in the mouth to trigger the appearance of stomatitis in individuals.